2021
DOI: 10.1007/s11605-020-04802-4
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Assisted Colonoscopy for Detection of Colon Polyps: a Prospective, Randomized Cohort Study

Abstract: Background and aims Improving the rate of polyp detection is an important measure to prevent colorectal cancer (CRC). Real-time automatic polyp detection systems, through deep learning methods, can learn and perform specific endoscopic tasks previously performed by endoscopists. The purpose of this study was to explore whether a high-performance, real-time automatic polyp detection system could improve the polyp detection rate (PDR) in the actual clinical environment. Methods The selected patients underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…Finally, AI algorithms have been previously applied to enhance the detection of colonic polyps[ 87 ] and distinguish among subtypes of neoplastic colorectal lesions[ 88 ] in the general population. Although patients with IBD who have extensive colitis have a significantly greater risk of colorectal cancer compared to the general population [ 89 , 90 ], there have been limited studies applying AI technologies to improve colorectal cancer surveillance or develop prediction risk models in patients with IBD.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, AI algorithms have been previously applied to enhance the detection of colonic polyps[ 87 ] and distinguish among subtypes of neoplastic colorectal lesions[ 88 ] in the general population. Although patients with IBD who have extensive colitis have a significantly greater risk of colorectal cancer compared to the general population [ 89 , 90 ], there have been limited studies applying AI technologies to improve colorectal cancer surveillance or develop prediction risk models in patients with IBD.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in this systematic review included preclinical studies for polyp detection (Table 1 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]), preclinical studies for polyp characterization (Table 2 [11,13,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]), and recent RCTs (Table 3 [56][57][58][59][60][61][62][63]). The studies were all published between 2003 and 2020.…”
Section: Search Results and Characteristicsmentioning
confidence: 99%
“…A number of research studies have already suggested AI has the potential to transform the healthcare sector particularly in areas where image recognition can be applied [ 35 37 ]. In terms of colorectal diseases, AI has been applied to colonic polyps, adenomas, colorectal cancer, ulcerative colitis and intestinal motility disorders [ 38 41 ]. Owing to the rapid development of AI technology, AI is bound to continually play an important role in the field of colorectal diagnosis and treatment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%